Treatment of severe steroid dependent preschool asthma with nebulised budesonide suspension. Issue 3 (March 1993) - Ilangovan, P; Pedersen, S; Godfrey, S; Nikander, K; Noviski, N; Warner, J O
Abstract : The steroid sparing effect of nebulised budesonide suspension was assessed in a double blind placebo controlled parallel group study of 36 preschool children with severe asthma who were dependent on treatment with oral steroids. Nebulised budesonide suspension significantly reduced the requirement for treatment with oral steroids, and produced a marked improvement in overall health as scored on a visual analogue scale during the clinic visits. This study shows a significant step forward in the prophylactic treatment of asthma in children under the age of 3 years, in whom the efficacy of many other nebulised treatments has been questioned.